Three-dimensional flow light anti-counterfeiting ink, silver light column film and preparation method thereof
Patent Information
- Application Number
- CN202611237548.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-20
AI Technical Summary
1.解决普通银色片状颜料缺少磁响应能力,而直接附着磁性颗粒又容易降低反射率的问题;
[0108]与现有技术相比,本发明提供了立体流光防伪油墨、银色光柱膜及其制备方法,具备以下有益效果:采用由片状透明基体、磁响应层、介质间隔层、银色反射层和透明保护层构成的核壳型颜料,实现了磁响应能力、银色反射能力及固化网络结合能力的统一。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the fields of optical anti-counterfeiting materials, magnetically responsive functional pigments, radiation-cured inks, and microstructured functional thin films, and particularly to a three-dimensional flowing light anti-counterfeiting ink containing a core-shell type magnetically responsive silver flake pigment, a silver light column film formed using the three-dimensional flowing light anti-counterfeiting ink, and a method for preparing the same. Background Technology
[0002] Silver powder, aluminum powder, silver-plated glass flakes, pearlescent pigments, and magnetic photochromic pigments have been used in packaging printing and security anti-counterfeiting fields. The spatial orientation of flake pigments in the ink layer directly affects the reflectivity, shimmering effect, and viewing angle response of the coating.
[0003] In the printing or coating process, traditional silver inks mainly rely on the coating shearing action to make the flake-like pigments tend to align parallel to the substrate surface. This alignment can improve the metallic brightness on the front, but the pigment orientation is usually basically uniform or fluctuates irregularly, making it difficult to form a continuously changing reflection angle distribution along the film surface. Therefore, it can usually only produce ordinary silver flashes or local light and dark variations, and it is difficult to form a light column with clear boundaries, continuous movement and a sense of depth.
[0004] Magnetic optically variable inks can control the orientation of magnetic flake pigments using an external magnetic field. However, ordinary bar magnets, devices with alternating adjacent magnetic poles, or devices with a single-direction magnetic field can usually only create a uniform magnetic field or a locally discrete magnetic field. Flake pigments tend to form segmented orientations in regions corresponding to different magnetic poles, leading to problems such as broken stripes, abrupt changes in light pillars, or obvious periodic boundaries in the optical pattern.
[0005] If high irradiation energy is used for complete curing immediately after magnetic field orientation, the number of reactive groups remaining on the ink layer surface will decrease, making it easy for the interlayer adhesion between the subsequent transparent micro-optical modulation layer and the directional reflection layer to decrease. Conversely, if the initial curing degree is too low, the pigment may rotate and settle after leaving the magnetic field due to flow, gravity, thermal motion, or internal layer stress, which will destroy the already formed continuous orientation structure.
[0006] Furthermore, when magnetic particles are directly attached to the surface of the silver reflective pigment, the magnetic particles may obscure the reflective interface and cause light scattering, thereby reducing the brightness of the silver. When the magnetic response layer is in direct contact with the silver or aluminum reflective layer, it may also cause interfacial reactions, reduced storage stability, or attenuation of reflectivity.
[0007] When silver is used as the reflective layer material, it may discolor in sulfur-containing gases, chlorine-containing media, or high-humidity environments. Simply setting a transparent protective layer without specifying the interface passivation method of the silver layer, the density of the protective layer, and its anti-discoloration effect makes it difficult to fully explain the optical stability of the silver reflective layer under long-term use conditions.
[0008] Existing technologies for the disclosure of gradient magnetic field orientation devices are often too general. For example, they only describe the use of "changing magnetic field" or "gradient magnetic field" to orient magnetic pigments, but do not specify the specific meaning of the magnet arrangement, magnetization direction, spacing between adjacent magnets, working distance, magnetic induction intensity, and magnetic field gradient. It is difficult for those skilled in the art to stably reproduce the continuous stream structure.
[0009] Furthermore, the radius of curvature, refractive index, bow height, pitch, and focal plane position of the cylindrical microlens directly affect the converging position and width of the light column. Simply specifying that the equivalent focal plane is located within or near the directional reflective layer, without explaining the calculation or design method of the equivalent focal length, may still result in insufficient disclosure of the optical structure.
[0010] Therefore, there is a need for an anti-counterfeiting ink that can take into account magnetic responsiveness, silver reflectivity, colorfastness, continuous orientation retention capability, and interlayer adhesion, and to provide a matching gradient magnetic field orientation device, staged curing process, and cylindrical microlens structure to form a continuously moving, high-brightness, clear-boundary, and durable three-dimensional silver light column. Summary of the Invention
[0011] The technical problems to be solved by this invention include: 1. Solve the problem that ordinary silver flake pigments lack magnetic responsiveness, while directly attaching magnetic particles can easily reduce reflectivity; 2. Solve the problem that ordinary magnetic field devices can only form uniform or discrete orientations, and it is difficult to form silver reflective structures with continuous angular changes; 3. Solve the problem of the mutual constraints between the degree of pigment orientation fixation, the surface reactivity of the ink layer, and the adhesion of the subsequent transparent micro-optical modulation layer; 4. Solve the problem that it is difficult to form a high-brightness, narrow-width three-dimensional light column by relying solely on magnetic orientation; 5. Solve the problem that the silver reflective layer is prone to discoloration and reduced reflectivity in sulfur-containing, high-humidity, or salt spray environments; 6. Clarify the definitions and measurement methods of gradient magnetic field, magnetic field gradient, signed deflection angle, and equivalent focal length of cylindrical microlens to improve the feasibility and repeatability of technical solutions.
[0012] To achieve the above objectives, the present invention provides the following technical solution: three-dimensional flowing light anti-counterfeiting ink.
[0013] By weight percentage, the three-dimensional luminous anti-counterfeiting ink comprises: 45%–70% photocurable film-forming component, 10%–25% reactive diluent, 8%–20% core-shell magnetically responsive silver flake pigment, 1%–5% photoinitiator, 0.2%–3% rheology orientation aid, 0.2%–2% dispersing and wetting agent, and functional aids, with the sum of all components being 100%.
[0014] In a preferred embodiment, the content of the functional additive is 0.2% to 5%, including one or more of leveling agents, defoamers, polymerization inhibitors, light stabilizers, and adhesion promoters.
[0015] The photocurable film-forming component includes aliphatic polyurethane acrylate and hyperbranched polyester acrylate, wherein the mass ratio of aliphatic polyurethane acrylate to hyperbranched polyester acrylate is 2:1 to 8:1.
[0016] The reactive diluent is selected from at least two of isoborneol acrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, and tripropylene glycol diacrylate.
[0017] The photoinitiator includes one or more of 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, and diacid phosphine oxide.
[0018] The rheology-oriented additives include one or more of hydrophobic fumed silica, modified urea rheology modifiers, polyamide waxes, and organobentonite.
[0019] The core-shell type magnetically responsive silver flake pigment includes a flake-shaped transparent substrate and, from the inside out, a magnetically responsive layer, a dielectric spacer layer, a silver reflective layer, and a transparent protective layer containing polymerizable groups, which are sequentially coated on the surface of the flake-shaped transparent substrate.
[0020] The sheet-like transparent substrate is a borosilicate glass sheet or a synthetic mica sheet, with a median particle size D50 of 8–35 μm and a thickness of 0.2–1.0 μm.
[0021] The magnetic response layer comprises at least one of iron oxide and ferrite, and has a thickness of 10–80 nm.
[0022] The dielectric spacer layer comprises at least one of silicon dioxide and aluminum oxide, and has a thickness of 20–150 nm.
[0023] The silver reflective layer comprises at least one of silver and aluminum, and has a thickness of 20–120 nm.
[0024] The total thickness of the transparent protective layer is 10-100 nm, including a silicon dioxide layer containing polymerizable groups, an organosilicon layer, or an organic-inorganic hybrid layer.
[0025] When the silver reflective layer is made of silver, the transparent protective layer preferably includes an interface passivation sublayer disposed adjacent to the silver reflective layer, and a transparent encapsulation sublayer containing polymerizable groups located outside the interface passivation sublayer.
[0026] The interface passivation sublayer is formed on the silver surface by a nitrogen-containing heterocyclic passivating agent, a mercaptosilane coupling agent, or a combination thereof, and the thickness is preferably 0.5 to 5 nm.
[0027] The nitrogen-containing heterocyclic passivating agent is selected from at least one of benzotriazole, 1,2,4-triazole, imidazole and their derivatives.
[0028] The transparent encapsulation sublayer comprises a silica layer modified with a methacryloyloxysilane coupling agent or an organic-inorganic hybrid layer.
[0029] The interface passivation sublayer is used to reduce direct contact between sulfur- or chlorine-containing media and the silver reflective layer, while the transparent encapsulation sublayer is used to further block corrosive media and copolymerizes with the ink resin network through its polymerizable groups.
[0030] When the silver reflective layer is made of aluminum, a nitrogen-containing heterocyclic passivation sublayer can be omitted, and a transparent encapsulation layer containing polymerizable groups can be directly formed outside the aluminum reflective layer. Using an aluminum reflective layer can serve as an alternative to a silver reflective layer, adapting to applications requiring high stability in sulfur-containing environments.
[0031] The dielectric spacer layer separates the magnetic response layer from the silver reflective layer, thereby reducing the light absorption and blocking of the silver reflective layer by the magnetic response layer and reducing the interfacial interaction between the magnetic response layer and the silver reflective layer.
[0032] The core-shell type magnetically responsive silver flake pigment has a saturation magnetization of 4–18 emu / g and an average reflectivity of not less than 60% in the 450–700 nm wavelength band.
[0033] The three-dimensional luminous anti-counterfeiting ink has a yield stress of 2-20 Pa at 25°C, and its viscosity recovery rate after shearing and standing for 60 seconds is not less than 70%.
[0034] This rheological property gives the ink appropriate fluidity during coating and magnetic field orientation, allowing the flake pigments to rotate under the action of magnetic torque; after the pigments are oriented, the viscosity of the ink can recover quickly, thereby reducing the rotation and sedimentation of the flake pigments.
[0035] Silver light beam film The present invention also provides a silver light pillar film, comprising a transparent base film, a base coating layer, a directional reflective layer and a transparent micro-optical modulation layer stacked sequentially.
[0036] The transparent base film is selected from one of polyethylene terephthalate film, biaxially oriented polypropylene film, polycarbonate film and polyamide film, and has a thickness of 12 to 100 μm.
[0037] The thickness of the base coating is 0.3 to 3 μm.
[0038] The thickness of the directional reflective layer is 2 to 20 μm, and it is formed by the three-dimensional flowing light anti-counterfeiting ink through magnetic field orientation and first photocuring.
[0039] The thickness of the transparent micro-optical modulation layer is 25–200 μm, and a parallel array of cylindrical microlenses is disposed on the side of the layer opposite to the directional reflection layer.
[0040] The cylindrical microlens array has a pitch of 30–150 μm, an arc height of 5–40 μm, and a radius of curvature of 15–100 μm.
[0041] The angle between the extension direction of the cylindrical microlens and the first direction is 70° to 90°.
[0042] The equivalent focal plane of the cylindrical microlens array is located within the directional reflection layer, or the distance between the equivalent focal plane and the directional reflection layer is no greater than 15% of the equivalent focal length of the cylindrical microlens.
[0043] The refractive index of the transparent micro-optical modulation layer is preferably 1.48 to 1.58.
[0044] A transparent wear-resistant layer may also be provided outside the transparent micro-optical modulation layer. The transparent wear-resistant layer conformally covers the surface of the cylindrical microlens and does not completely fill the valley between adjacent cylindrical microlenses, with a thickness of 0.5 to 5 μm.
[0045] Definitions of the first direction and the signed deflection angle The plane containing the silver light pillar film is defined as the XY plane, and the thickness direction of the silver light pillar film is defined as the Z direction.
[0046] The direction in which the pigment continuously changes orientation within the silver light column film is defined as the first direction, and a predetermined direction of the first direction is defined as the +X direction, and the direction opposite to the +X direction is defined as the -X direction.
[0047] The plane formed by the first direction X and the normal Z of the membrane surface is defined as the orientation plane, i.e., the XZ plane.
[0048] The normal of the core-shell type magnetically responsive silver flake pigment lies within the orientation plane.
[0049] The signed deflection angle θ refers to the directional angle between the normal of the core-shell magnetically responsive silver flake pigment and the normal of the silver beam film surface.
[0050] When the normal of the flake pigment deflects from the normal of the film surface toward the +X side of the first direction, θ takes a positive value; When the normal of the flake pigment deflects from the film surface normal to the -X side of the first direction, θ takes a negative value; When the normal of the flake pigment coincides with the normal of the film surface, θ is 0°.
[0051] The signed deflection angle θ is -35° to +35°.
[0052] The signed deflection angle changes periodically and continuously along the first direction. Within one orientation period, the signed deflection angle can continuously increase from a negative value to a positive value, and then continuously decrease from a positive value to a negative value.
[0053] The change of the signed deflection angle with respect to the position in the first direction can be an approximate triangular wave, sine wave, sawtooth wave, or a periodic function composed of continuous curve segments.
[0054] The orientation period is 0.8–10 mm.
[0055] The gradient of the signed deflection angle along the first direction refers to the absolute value of the rate of change of the signed deflection angle relative to the position in the first direction. When using discrete measurements, its calculation formula is:
[0056] In the formula: This represents the gradient of the signed deflection angle between adjacent measurement positions, in ° / mm. and These are the signed deflection angles of the flake pigments at adjacent positions; This represents the distance between adjacent measurement locations along the first direction.
[0057] The gradient of the signed deflection angle is 2° / mm to 20° / mm.
[0058] Definition of magnetic field gradient The gradient magnetic field orientation device generates a magnetic induction intensity vector on the working plane where the ink layer is located:
[0059] Since the pigment mainly rotates within the directional plane formed by the first direction and the normal to the film surface, it is preferable to make... The component is less than 10% of the magnetic flux density modulus.
[0060] The term "magnetic field gradient" as used in this invention refers to the magnitude of magnetic induction intensity. The absolute value of the spatial rate of change along the first direction X, in mT / mm.
[0061] When represented continuously, the magnetic field gradient is defined as:
[0062] When using discrete measurements, the local magnetic field gradient is calculated according to the following formula: The 5-35 mT / mm mentioned in this invention refers to the arithmetic mean obtained after obtaining multiple local magnetic field gradients with a measurement interval of 0.5-1 mm within the effective working area corresponding to an orientation period.
[0063] Magnetic field direction angle Calculate according to the following formula:
[0064] The magnetic field direction is positive when it deflects from the normal to the membrane surface towards the +X direction, and negative when it deflects towards the -X direction.
[0065] The rate of change of magnetic field direction and the magnetic field gradient are different parameters. The magnetic field gradient characterizes the change in the magnitude of magnetic induction intensity along the first direction, while the rate of change of magnetic field direction is used to characterize the degree of continuous rotation of the magnetic field vector direction along the first direction.
[0066] Cylindrical microlens equivalent focal length and focal plane design Cylindrical microlenses are used to converge reflected light in a cross section perpendicular to the extension direction of the cylindrical microlens, forming a linear focal spot.
[0067] For a plano-convex cylindrical microlens with its curved surface facing the air and its other side approximately flat, under paraxial and thin lens approximation conditions, its equivalent focal length... A preliminary calculation can be performed using the following formula:
[0068] In the formula: This is the equivalent focal length of the cylindrical microlens; Let be the radius of curvature of the cylindrical microlens surface; The refractive index of the transparent micro-optical modulation layer at the designed wavelength; denoted as , where is the refractive index of the medium on the outer side of the cylindrical microlens.
[0069] When the outer side of the cylindrical microlens is air. Approximating 1, the above formula can be simplified to: When the effective aperture of a cylindrical microlens is approximately equal to its pitch Its radius of curvature It can also be determined according to the pitch and bow height using the following formula: In the formula: The pitch of the cylindrical microlens; The height of the cylindrical microlens.
[0070] The above formula is used for the preliminary design of cylindrical microlens parameters. Considering that the transparent micro-optical modulation layer has a finite thickness, and that a base resin, a directional reflection layer, and a transparent substrate are also disposed below it, the actual equivalent focal plane position should be further corrected by ray tracing using Snell's law based on the refractive index, layer thickness, radius of curvature, and incident angle of each layer.
[0071] Once the design is complete, the actual equivalent focal plane can be determined by moving the microscopic imaging surface along the thickness direction or by using an optical focal scanning device to measure the location of the minimum width of the line focal spot.
[0072] The equivalent focal plane of the cylindrical microlens array is designed to be located within the directional reflection layer, or at a distance from the directional reflection layer not exceeding 15% of the equivalent focal length of the cylindrical microlens, thereby improving the peak brightness of the light column and reducing the light column broadening caused by focus deviation.
[0073] Gradient magnetic field orientation device The gradient magnetic field orientation device includes a non-magnetic mounting base, multiple strip permanent magnet units, and positioning slots for fixing the strip permanent magnet units.
[0074] Each strip permanent magnet unit is arranged sequentially along the first direction within the transparent base film.
[0075] The length direction of each strip permanent magnet unit is parallel to the second direction, which is located in the film surface and perpendicular to the first direction.
[0076] The strip permanent magnet unit preferably uses neodymium iron boron permanent magnets. The length of the strip permanent magnet unit along the second direction is 20-100 mm, the width along the first direction is 3-20 mm, and the thickness is 2-10 mm.
[0077] The magnetization direction of each bar permanent magnet unit is located in the orientation plane formed by the normal of the film surface and the first direction.
[0078] The included angle between the magnetization directions of two adjacent bar permanent magnet units is 5° to 30°, and the magnetization directions of multiple bar permanent magnet units change sequentially along the first direction in the same rotation direction.
[0079] The center distance between two adjacent strip permanent magnet units is 5 to 30 mm.
[0080] The magnetic fields generated by each bar permanent magnet unit are superimposed, causing the direction of the magnetic field vector at the location of the uncured ink layer to change continuously along the first direction, reducing abrupt changes in the magnetic field direction at the boundary of adjacent magnets.
[0081] In one embodiment, the gradient magnetic field orientation device further includes a soft magnetic conductive plate disposed on the side of the bar permanent magnet unit near the ink layer.
[0082] The soft magnetic conductive plate is made of pure iron, silicon steel, permalloy or soft magnetic composite material.
[0083] Multiple magnetic guide teeth extending along a second direction are provided on the soft magnetic guide plate, with a pitch of 0.8–10 mm between adjacent magnetic guide teeth. The height, width, or tilt angle of the magnetic guide teeth are periodically changed along a first direction to shape the magnetic flux generated by the bar permanent magnet unit.
[0084] When a pigment orientation period smaller than the center distance of a permanent magnet is required, a soft magnetic plate with periodic magnetic teeth can be used to create a magnetic field direction change period of 0.8 to 10 mm at the location of the ink layer.
[0085] In another embodiment, a first permanent magnet array and a second permanent magnet array corresponding to each other can be set on both sides of the transparent base film. By coordinating the magnetization directions of the upper and lower permanent magnet arrays, the horizontal component, vertical component and magnetic field gradient of the magnetic field can be adjusted.
[0086] The distance between the working surface of the gradient magnetic field orientation device and the uncured ink layer is 1–8 mm.
[0087] The magnetic induction intensity at the location of the uncured ink layer is 60–250 mT, and the magnetic field gradient is 5–35 mT / mm.
[0088] The magnetic field component is measured along the first direction using a triaxial Hall probe. , and The measurement interval is 0.5 to 1 mm, and the magnetic flux density, magnetic field gradient and magnetic field direction angle are calculated according to the aforementioned formula.
[0089] Preparation method of silver beam film S1. Preparation of 3D Flowing Light Anti-counterfeiting Ink A core-shell magnetically responsive silver flake pigment, a portion of reactive diluent, and a dispersing and wetting agent are added to a dispersion container and premixed at 300–800 r / min for 10–30 min to obtain a pigment predispersion.
[0090] Aliphatic polyurethane acrylate, hyperbranched polyester acrylate, remaining reactive diluent, photoinitiator, rheology orientation agent and functional agent are added to the pigment predispersant and stirred for 20-60 minutes under light-protected conditions.
[0091] Vacuum degassing at -0.08 to -0.095 MPa for 5 to 20 minutes yields three-dimensional luminous anti-counterfeiting ink.
[0092] S2. Formation of an uncured ink layer The transparent base film is subjected to corona treatment, plasma treatment, or primer treatment.
[0093] A primer is applied to the surface of a transparent base film, and then dried with hot air or cured with ultraviolet light to form a primer layer with a thickness of 0.3–3 μm.
[0094] Using gravure coating, slot coating, flexographic printing or screen printing, a three-dimensional glossy anti-counterfeiting ink is coated on the surface of the base layer to form an uncured ink layer with a thickness of 3 to 20 μm.
[0095] S3. Magnetic field orientation and first photocuring The transparent base film, which forms an uncured ink layer, is passed through a gradient magnetic field orientation device at a speed of 5–60 m / min.
[0096] Under the influence of a gradient magnetic field, the core-shell magnetically responsive silver flake pigment rotates around its center, so that the normal of the flake pigment and the local magnetic field vector form a stable angular correspondence.
[0097] By adjusting the magnetization direction of the permanent magnet unit, the angle between adjacent magnetization directions, the center distance, the pitch of the magnetic teeth, and the distance between the device and the ink layer, the signed deflection angle of the flake pigment can be made to change periodically and continuously along the first direction.
[0098] Under the condition of maintaining a gradient magnetic field, the uncured ink layer is subjected to the first ultraviolet curing.
[0099] The wavelength of the first ultraviolet light is 365–405 nm, and the irradiation energy is 20–150 mJ / cm².
[0100] The first photocuring process enables the conversion rate of polymerizable unsaturated double bonds in the ink layer to reach 15% to 45%.
[0101] The conversion rate enables the ink layer to form a preliminary cross-linked network and fix the orientation of the flake pigments, while retaining unreacted double bonds to facilitate the subsequent co-curing of the transparent micro-optical modulation layer and the directional reflection layer.
[0102] S4. Formation of a transparent micro-optical modulation layer A transparent light-curing resin is applied to the surface of the directional reflective layer after the first light curing.
[0103] A microstructure mold with a cylindrical microlens negative shape on its surface is pressed onto the surface of a transparent photocurable resin.
[0104] The angle between the extension direction of the cylindrical microlens and the first direction is 70° to 90°.
[0105] The microstructure mold is kept in a pressed state for a second UV curing process, with the second UV curing irradiation energy being 300–1200 mJ / cm².
[0106] Remove the microstructure mold to form a cylindrical microlens array.
[0107] If necessary, a transparent wear-resistant coating with a thickness of 0.5–5 μm is applied to the surface of the cylindrical microlens array and then cured again.
[0108] Compared with the prior art, the present invention provides a three-dimensional flowing light anti-counterfeiting ink, a silver light column film and its preparation method, which has the following beneficial effects: by using a core-shell type pigment composed of a sheet-like transparent substrate, a magnetic response layer, a dielectric spacer layer, a silver reflective layer and a transparent protective layer, the magnetic response capability, silver reflective capability and curing network bonding capability are unified.
[0109] The dielectric spacer reduces the obstruction of the magnetic response layer on the silver reflective layer, enabling the core-shell magnetically responsive silver flake pigment to achieve an average visible light reflectance of not less than 60% while having a saturation magnetization of 4–18 emu / g.
[0110] For silver reflective layers, setting an interface passivation sublayer and a transparent encapsulation sublayer containing polymerizable groups on the outside can reduce the diffusion of sulfur-containing gases, water vapor and chlorine-containing media to the surface of the silver layer, thereby reducing silver layer discoloration and reflectivity attenuation.
[0111] For applications requiring high stability against discoloration, an aluminum reflective layer can be used instead of a silver reflective layer.
[0112] By continuously changing the direction of the magnetic field vector along the first direction, the flake pigment can form a continuous signed deflection angle distribution, reducing the orientation abrupt changes and light column jumps caused by ordinary alternating magnetic poles.
[0113] By controlling the ink yield stress to 2–20 Pa and the viscosity recovery rate to no less than 70%, the ink becomes oriented during the magnetic field and can suppress pigment rotation and sedimentation after leaving the magnetic field.
[0114] The first photocuring process controls the conversion rate of unsaturated double bonds to 15%–45%, which can both fix the orientation of the flake pigments and retain the reactive groups required for subsequent interlayer co-curing.
[0115] The cylindrical microlens array converges the angle-selective reflected light generated by the directional reflective layer, so that a wider flowing light area is concentrated to form a silver light pillar with clear boundaries, which improves the peak brightness of the light pillar, background contrast and three-dimensional depth. Attached Figure Description
[0116] Figure 1 This is a high-resolution transmission electron microscope image of the cross-section of the core-shell type magnetically responsive silver flake pigment of Embodiment 2 of the present invention; Figure 2 This is a STEM-EDS elemental distribution diagram of the cross-section of a core-shell magnetically responsive silver flake pigment according to Embodiment 2 of the present invention. Figure 3This is a hysteresis loop diagram of a vibrating sample magnetometer for a core-shell type magnetically responsive silver flake pigment according to Embodiment 2 of the present invention. Figure 4 This is a cross-sectional relative light intensity distribution diagram of the silver light column film cylindrical microlens of Embodiment 2 of the present invention. Detailed Implementation
[0117] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0118] Please see Figures 1-4 This invention provides a technical solution for three-dimensional luminous anti-counterfeiting ink, silver light column film, and their preparation method: Unless otherwise specified, all percentages are by mass.
[0119] Main raw materials Aliphatic polyurethane acrylates have a functionality of 2–6 and a viscosity of 3000–30000 mPa·s at 25°C.
[0120] The functionality of hyperbranched polyester acrylate is 6–16, and its viscosity at 25°C is 1000–15000 mPa·s.
[0121] The reactive diluent consists of isoborneol acrylate and 1,6-hexanediol diacrylate, with tripropylene glycol diacrylate added if necessary.
[0122] The photoinitiator consists of 2,4,6-trimethylbenzoyl diphenylphosphine oxide and 1-hydroxycyclohexylphenyl ketone.
[0123] The rheology orientation aid is composed of hydrophobic fumed silica and modified urea rheology modifier.
[0124] Functional additives include polyether-modified siloxane leveling agents, defoamers, adhesion promoters, and polymerization inhibitors.
[0125] Preparation of core-shell magnetically responsive silver flake pigments 1. Pretreatment of sheet-like transparent substrate Add borosilicate glass slides or synthetic mica sheets to an alkaline cleaning solution with a mass fraction of 2% and stir and clean at 40°C for 20 minutes.
[0126] Wash with deionized water until neutral, then wash with ethanol and dry at 80°C.
[0127] 2. Formation of a magnetic response layer The pretreated sheet-like transparent matrix was dispersed in deionized water.
[0128] According to Fe³ + with Fe² + Ferric chloride and ferrous chloride are added in a molar ratio of 2:1, and the mixture is heated to 65–80°C under nitrogen protection.
[0129] Add ammonia water dropwise to control the pH of the system to 9.0-10.5, and react for 30-120 minutes to allow ferric oxide particles to be deposited in situ on the surface of the sheet-like transparent substrate.
[0130] By controlling the amount of iron salt added and the reaction time, the thickness of the magnetic response layer can be controlled to be 10–80 nm.
[0131] After the reaction is complete, magnetic separation, washing, and drying are performed.
[0132] 3. Formation of a dielectric spacer layer The flake-shaped pigment coated with a magnetic response layer is dispersed in a mixture of ethanol, water, and ammonia.
[0133] Tetraethyl orthosilicate is added dropwise and reacted for 2–8 hours to form a silica dielectric spacer layer on the surface of the magnetic response layer.
[0134] The thickness of the dielectric spacer layer was controlled to be 20–150 nm by adjusting the amount of tetraethyl orthosilicate added and the reaction time.
[0135] 4. Formation of a silver reflective layer In one embodiment, silver is deposited on the surface of the dielectric spacer layer using magnetron sputtering.
[0136] During the sputtering process, the flake pigment is slowly turned over so that the silver layer covers the main surface of the flake pigment.
[0137] The thickness of the silver reflective layer was controlled to be 20–120 nm by adjusting the sputtering power and deposition time.
[0138] In another embodiment, a silver reflective layer is formed using a silver ammonia complex reduction method.
[0139] In another embodiment, an aluminum reflective layer is formed on the surface of the dielectric spacer layer by magnetron sputtering.
[0140] 5. Silver reflective layer with anti-discoloration passivation treatment When the silver reflective layer is made of silver, the flake-shaped pigment forming the silver reflective layer is immersed in a nitrogen-containing heterocyclic passivating agent solution with a mass fraction of 0.05% to 0.5% for 1 to 10 minutes.
[0141] The solvent for the nitrogen-containing heterocyclic passivating agent solution is ethanol, water, or a mixture of ethanol and water.
[0142] After treatment, the surface is quickly washed with ethanol and dried at 40–60°C to form an interface passivation sublayer with a thickness of 0.5–5 nm on the silver surface.
[0143] 6. Form a transparent encapsulation sublayer The passivated flake pigment was dispersed in an aqueous ethanol solution, methacryloyloxypropyltrimethoxysilane was added, and the pH was adjusted to 4.0–5.5.
[0144] The reaction is carried out at 40–60 °C for 2–6 h, causing the methacryloyloxy silane to hydrolyze and condense on the surface of the passivated silver reflective layer, forming a transparent encapsulation sublayer containing polymerizable groups.
[0145] The interface passivation sublayer and the transparent encapsulation sublayer together constitute a transparent protective layer, and the total thickness of the transparent protective layer is controlled to be 10-100nm.
[0146] When using an aluminum reflective layer, the nitrogen-containing heterocyclic passivation treatment can be omitted, and a transparent encapsulation layer containing polymerizable groups can be directly formed.
[0147] Different core-shell magnetically responsive silver flake pigments Core-shell magnetically responsive silver flake pigments P1 to P6 were prepared, and the specific parameters are shown in Table 1.
[0148] Table 1 Parameters of Core-Shell Magnetic-Responsive Silver Flake Pigments
[0149] 3D Flowing Light Anti-counterfeiting Ink Examples Example 1 Weigh the following components by mass percentage: The photocurable film-forming component is 45%, wherein the mass ratio of aliphatic polyurethane acrylate to hyperbranched polyester acrylate is 2:1. 25% reactive diluent; The core-shell type magnetically responsive silver flake pigment P1 is 20%; Photoinitiator 5%; 3% rheology-directing additive; Dispersant and wetting agent 1.5%; Functional additives 0.5%.
[0150] P1, reactive diluent, and dispersant / wetting agent were premixed at 500 rpm for 20 min, then other components were added, and the mixture was stirred for 40 min under light-protected conditions. Vacuum degassing was then performed for 10 min to obtain the three-dimensional luminous anti-counterfeiting ink of Example 1.
[0151] Example 2 Weigh the following components by mass percentage: The photocurable film-forming component is 57%, wherein the mass ratio of aliphatic polyurethane acrylate to hyperbranched polyester acrylate is 5:1. 20% reactive diluent; The core-shell magnetically responsive silver flake pigment has a P2 content of 15%. Photoinitiator 3%; 2% rheology-directing additive; 1% dispersant and wetting agent; Functional additives 2%.
[0152] The ink was prepared according to the method in Example 1.
[0153] Example 3 Weigh the following components by mass percentage: The photocurable film-forming component is 70%, in which the mass ratio of aliphatic polyurethane acrylate to hyperbranched polyester acrylate is 8:1. 10% reactive diluent; The core-shell magnetically responsive silver flake pigment has a P3 content of 8%. Photoinitiator 5%; 3% rheology-directing additive; 2% dispersant and wetting agent; Functional additives 2%.
[0154] The ink was prepared according to the method in Example 1.
[0155] Example 4 Weigh the following components by mass percentage: The photocurable film-forming component is 64.6%, of which the mass ratio of aliphatic polyurethane acrylate to hyperbranched polyester acrylate is 4:1; 25% reactive diluent; The core-shell magnetically responsive silver flake pigment P4 has an 8% content. Photoinitiator 1%; 0.2% rheology-directing agent; 0.2% dispersant and wetting agent; Functional additives 1%.
[0156] The ink was prepared according to the method in Example 1.
[0157] Example 5 Weigh the following components by mass percentage: Photocurable film-forming component: 60%; 15% reactive diluent; The core-shell magnetically responsive silver flake pigment P5 is 18%; Photoinitiator 2%; 1% rheology-directing agent; 1% dispersant and wetting agent; Functional additives 3%.
[0158] The ink was prepared according to the method in Example 1.
[0159] Example 6 Except for replacing the core-shell magnetically responsive silver flake pigment P2 in Example 2 with the core-shell magnetically responsive silver flake pigment P6 with an aluminum reflective layer, the composition and preparation process of the ink are the same as in Example 2.
[0160] Silver light column film example Example 1 A 12μm thick PET transparent base film is used, the bottom coating thickness is 0.3μm, and the uncured ink layer thickness is 3μm.
[0161] In the gradient magnetic field orientation device, the magnetization direction of adjacent permanent magnet units is 5° and the center distance is 5mm.
[0162] The magnetic induction intensity at the ink layer position is 60mT, the magnetic field gradient is 5mT / mm, the working distance is 8mm, and the transparent base film conveying speed is 5m / min.
[0163] The energy of the first photopolymerization irradiation was 20 mJ / cm².
[0164] The pigment's sign deflection angle varies continuously between -12.5° and +12.5°, with an orientation period of 5 mm and an angle change gradient of 10° / mm.
[0165] The cylindrical microlens array has a pitch of 30 μm, an arc height of 5 μm, a radius of curvature of 25 μm, and an angle of 70° between its extension direction and the first direction.
[0166] The thickness of the transparent micro-optical modulation layer is 15μm, the energy of the second photocuring irradiation is 300mJ / cm², and the thickness of the transparent wear-resistant layer is 0.5μm.
[0167] Example 2 A 50μm thick PET transparent base film is used, the bottom coating thickness is 1.5μm, and the uncured ink layer thickness is 15μm.
[0168] The magnetization direction of adjacent permanent magnet units is 15° and the center distance is 15mm.
[0169] The magnetic induction intensity at the ink layer position is 150mT, the magnetic field gradient is 20mT / mm, the working distance is 4mm, and the transparent base film conveying speed is 30m / min.
[0170] The first photocuring irradiation energy was 80 mJ / cm², and the thickness of the directional reflective layer after the first photocuring was 13–14.5 μm.
[0171] The pigment's sign deflection angle changes continuously between -35° and +35°, with an orientation period of 7 mm and an angle change gradient of 20° / mm.
[0172] The direction change unit of the soft magnetic conductive plate has a period of 7 mm, and each unit period is equipped with 8 magnetic teeth.
[0173] The cylindrical microlens array has a pitch of 80 μm, an arc height of 15 μm, a radius of curvature of 60.8 μm, and an angle of 80° between its extension direction and the first direction.
[0174] The thickness of the transparent micro-optical modulation layer is 105–125 μm, the energy of the second photocuring irradiation is 700 mJ / cm², and the thickness of the transparent wear-resistant layer is 2.5 μm.
[0175] Example 3 A 100μm thick transparent polycarbonate base film is used, the bottom coating layer is 3μm thick, and the uncured ink layer is 20μm thick.
[0176] The magnetization direction of adjacent permanent magnet units is 30° and the center distance is 30mm.
[0177] The magnetic induction intensity at the ink layer position is 250mT, the magnetic field gradient is 35mT / mm, the working distance is 1mm, and the transparent base film conveying speed is 60m / min.
[0178] The energy of the first photopolymerization irradiation was 150 mJ / cm².
[0179] The pigment's sign deflection angle changes continuously between -5° and +5°, with an orientation period of 10 mm and an angle change gradient of 2° / mm.
[0180] The cylindrical microlens array has a pitch of 150 μm, an arc height of 33.9 μm, a radius of curvature of 100 μm, and an angle of 90° between its extension direction and the first direction.
[0181] The thickness of the transparent micro-optical modulation layer is 80 μm, the energy of the second photocuring irradiation is 1200 mJ / cm², and the thickness of the transparent wear-resistant layer is 5 μm.
[0182] Example 4 A 25μm thick PET transparent base film is used, the bottom coating thickness is 0.8μm, and the uncured ink layer thickness is 5μm.
[0183] The magnetization direction of adjacent permanent magnet units is 10° and the center distance is 10mm.
[0184] A soft magnetic conductive plate with magnetic teeth is placed between the permanent magnet array and the ink layer, with a tooth pitch of 0.8 mm.
[0185] The magnetic induction intensity at the ink layer position is 100mT, the magnetic field gradient is 15mT / mm, the working distance is 5mm, and the transparent base film conveying speed is 20m / min.
[0186] The energy of the first photopolymerization irradiation was 50 mJ / cm².
[0187] The pigment's sign deflection angle varies continuously between -4° and +4°, with an orientation period of 0.8 mm and an angle change gradient of 20° / mm.
[0188] The direction change unit has a period of 0.8 mm, and each period has 4 to 8 miniature magnetic teeth.
[0189] The cylindrical microlens array has a pitch of 30 μm, an arc height of 15 μm, a radius of curvature of 15 μm, and an angle of 75° between its extension direction and the first direction.
[0190] The thickness of the transparent micro-optical modulation layer is 25 μm, the energy of the second photocuring irradiation is 500 mJ / cm², and the thickness of the transparent wear-resistant layer is 1 μm.
[0191] Example 5 A 75μm thick polyamide transparent base film is used, the bottom coating thickness is 2μm, and the uncured ink layer thickness is 15μm.
[0192] The magnetization direction of adjacent permanent magnet units is 20° and the center distance is 20mm.
[0193] The magnetic induction intensity at the ink layer position is 200mT, the magnetic field gradient is 28mT / mm, the working distance is 2mm, and the transparent base film conveying speed is 45m / min.
[0194] The energy of the first photopolymerization irradiation was 120 mJ / cm².
[0195] The pigment's sign deflection angle changes continuously between -12° and +12°, with an orientation period of 4 mm and an angle change gradient of 12° / mm.
[0196] The cylindrical microlens array has a pitch of 100 μm, an arc height of 40 μm, a radius of curvature of 51.3 μm, and an angle of 85° between its extension direction and the first direction.
[0197] The thickness of the transparent micro-optical modulation layer is 60μm, the energy of the second photocuring irradiation is 1000mJ / cm², and the thickness of the transparent wear-resistant layer is 4μm.
[0198] Example 6 The aluminum-containing reflective layer ink of Example 6 was used.
[0199] Except for replacing P2 with P6 for the core-shell type magnetically responsive flake pigment, the parameters of the transparent base film, the base coating, the gradient magnetic field, the first photocuring, the cylindrical microlens array, the second photocuring, and the transparent wear-resistant layer are all the same as in Example 2.
[0200] Comparative Example 1: In Example 2, P2 was replaced with a silver flake pigment that had the same particle size, matrix thickness, dielectric spacer layer, silver reflective layer, interface passivation sublayer, and transparent encapsulation sublayer, but without the magnetite (Fe3O4) magnetic response layer. The saturation magnetization of the non-magnetic silver flake pigment, measured using a vibrating sample magnetometer, was 0.03 emu / g, close to the instrument's detection limit, and can be considered as lacking effective magnetic responsiveness. Other ink compositions, magnetic field devices, curing parameters, and microlens parameters were the same as in Example 2.
[0201] Comparative Example 2: The ink composition and other processes were the same as in Example 2. The gradient magnetic field orientation device was replaced with a parallel magnetic pole device whose magnetic field direction remained unchanged, and the magnetic induction intensity at the ink layer location remained 150 mT.
[0202] Comparative Example 3 had the same ink composition, pigment orientation, and curing energy as Example 2.
[0203] The transparent micro-optical modulation layer with a cylindrical microlens array is replaced with a planar transparent layer of the same material and the same average thickness.
[0204] Comparative Example 4 was identical to Example 2 except that the energy of the first photocuring irradiation was adjusted from 80 mJ / cm² to 10 mJ / cm².
[0205] Comparative Example 5 was identical to Example 2 except that the energy of the first photocuring irradiation was adjusted from 80 mJ / cm² to 200 mJ / cm².
[0206] Comparative Example 6 was identical to Example 2 except that 2% of the rheology orientation agent was not added and the photocurable film-forming component was increased from 57% to 59% to maintain a total of 100%.
[0207] Comparative Example 7 is identical to Example 2 except that the magnetization direction angle between two adjacent bar permanent magnet units is adjusted from 15° to 45°.
[0208] Comparative Example 8 was identical to Example 2 except for omitting the nitrogen-containing heterocyclic passivation treatment of the silver reflective layer. Other parameters, including pigment structure, transparent encapsulation sublayer thickness, ink composition, and silver column film preparation parameters, were the same. To maintain a consistent total thickness of the transparent protective layer, the thickness corresponding to the omitted interface passivation sublayer was added to the transparent encapsulation sublayer.
[0209] Comparative Example 9, except for omitting the transparent protective layer on the outside of the P2 pigment silver reflective layer, has the same pigment structure, ink composition, and silver column film preparation parameters as in Example 2.
[0210] Performance testing 1. Ink rheological property testing The rheological properties of inks were tested using a rotational rheometer, in accordance with GB / T 10247—2008 "Methods for Viscosity Measurement".
[0211] The test temperature was 25℃, the parallel plate diameter was 25mm, and the test gap was 0.5mm. The test duration was 0.01~100s. - The shear rate of ¹ was scanned to obtain the flow curve and determine the yield stress.
[0212] Viscosity recovery rate was determined using a three-stage shear method: In the first stage, at 0.1s - ¹Hold the sample for 60 seconds and record the initial viscosity η0; The second stage, in 100s - ¹Hold the position for 30 seconds to simulate the high shear force experienced during ink coating; In the third stage, the shear rate is restored to 0.1 s. - ¹Hold the viscosity for 60 seconds and record the viscosity η at the 60th second. 60 .
[0213] Viscosity recovery rate is calculated using the following formula:
[0214] 2. Saturation magnetization test The hysteresis loop of a core-shell magnetically responsive flake pigment was tested using a vibrating sample magnetometer.
[0215] The test temperature was 25℃, and the applied magnetic field scanning range was -2T to +2T. The value of the magnetization intensity after it stabilized in the high magnetic field region was taken as the saturation magnetization intensity.
[0216] Each pigment was tested in triplicate, and the arithmetic mean was taken.
[0217] 3. Unsaturated double bond conversion rate test Referring to GB / T 6040—2019 "General Rules for Infrared Spectroscopic Analysis Methods", the conversion rate of unsaturated double bonds in the ink layer before and after the first photocuring was tested using ATR-FTIR.
[0218] Record 810cm respectively - ¹The characteristic peaks of unsaturated double bonds of acrylates near 1720 cm⁻¹ - ¹The carbonyl internal standard peak near the α group.
[0219] The conversion rate C of unsaturated double bonds is calculated according to the following formula:
[0220] Five different locations were selected for testing on each sample, and the arithmetic mean was taken.
[0221] Table 2. First Curing Energy and Unsaturated Double Bond Conversion Rate
[0222] 4. Magnetic field gradient and magnetic field direction continuity test The three components of magnetic induction intensity, Bx, By, and Bz, are measured in the working plane containing the uncured ink layer using a triaxial Hall probe.
[0223] The measurement interval along the first direction is 0.5 mm.
[0224] The magnitude of magnetic flux density is calculated according to the following formula:
[0225] The magnetic field gradient referred to in this invention is the absolute value of the spatial rate of change of the magnetic flux density modulus along the first direction X. During discrete measurements, the local magnetic field gradient is calculated according to the following formula:
[0226] The arithmetic mean of the absolute values of the local magnetic field gradients within one orientation period is taken as the magnetic field gradient test result of the sample.
[0227] The magnetic field direction angle is calculated using the following formula:
[0228] The maximum difference in magnetic field direction angle between adjacent measurement positions is taken as the maximum magnetic field direction step. The smaller the maximum magnetic field direction step, the more continuous the change in magnetic field direction along the first direction.
[0229] Table 3 Test results of the gradient magnetic field orientation device
[0230] 5. Pigment Orientation Angle Test The silver light column film was cut along the first direction to prepare a cross-sectional sample.
[0231] The directional reflective layer was observed using a scanning electron microscope or a high-resolution optical microscope. At least 20 measurement positions were selected at equal intervals within one orientation period to identify the main surface orientation of the flake pigment and to calculate the signed deflection angle of the normal of the flake pigment relative to the normal of the film surface.
[0232] The measured signed deflection angle is compared with the set angle curve to calculate the average absolute orientation error.
[0233] 6. Dynamic optical performance test of silver light beam Test lighting and geometry conditions shall be in accordance with GB / T 3978—2008, and object color and reflectance optical measurements shall be in accordance with GB / T3979—2008.
[0234] Under D65 standard lighting conditions, the incident light is located in the directional plane and the incident angle is 30°.
[0235] The sample was mounted on an electrically controlled rotating stage, and the observation angle was changed from -30° to +30°. A sample surface brightness image was acquired every 1°.
[0236] The centroid position of the brightness peak of the silver light column is determined based on the brightness image, and the effective displacement of the light column, the peak-to-back brightness ratio, and the maximum single-step jump variable are calculated.
[0237] 7. Average reflectance test Referring to the lighting and measurement conditions specified in GB / T 3978—2008 and GB / T 3979—2008, the spectral reflectance in the range of 450–700 nm was tested using a spectrophotometer with an integrating sphere, and the average reflectance was calculated.
[0238] 8. Transmittance and haze test of transparent layer Referencing GB / T 2410—2008, test the transmittance and haze of the transparent micro-optical modulation layer in areas without a directional reflective layer.
[0239] 9. Adhesion Test Referring to GB / T 9286—2021, a crisscross cutter with a spacing of 1 mm is used to cut through the transparent micro-optical modulation layer and the directional reflection layer to the surface of the transparent base film.
[0240] The test results are divided into 0 to 5 levels, with the lower the level indicating better adhesion.
[0241] 10. Pencil Hardness Test The surface hardness of the silver light pillar film was tested according to GB / T 6739—2022.
[0242] 11. Wear resistance test According to GB / T 1768—2006, the test was conducted using a CS-10 grinding wheel, a 500g load, and 500 revolutions.
[0243] Record the wear mass loss and remeasure the peak-to-back brightness ratio after the wear resistance test.
[0244] Optical retention rate is calculated using the following formula:
[0245] 12. Solvent resistance wiping test Referring to GB / T 23989—2009, the film layer was repeatedly wiped with cotton cloth soaked in methyl ethyl ketone.
[0246] One round trip is counted as one double-rub cycle. Record the number of double-rub cycles when the film layer shows signs of exposure to the substrate, significant loss of gloss, wrinkling, or delamination; if failure does not occur after 200 cycles, it is recorded as ">200".
[0247] 13. Sulfur-containing gas anti-discoloration test In accordance with the principles of GB / T 2423.51—2020 regarding gas control, temperature and humidity control, sample arrangement and exposure management in test chambers, a supplementary accelerated exposure test using a single hydrogen sulfide gas was set up.
[0248] The test conditions are as follows: The hydrogen sulfide concentration was 10 ± 2 ppm; The temperature is 25±2℃; The relative humidity is 75% ± 5%. The exposure time was 48 hours. The gas flows continuously and the concentration inside the chamber remains stable.
[0249] Before and after the test, the color parameters and average reflectance of the samples in the range of 450–700 nm were measured in accordance with GB / T 3978—2008 and GB / T 3979—2008.
[0250] Color difference is calculated using the following formula:
[0251] The reflectivity retention rate is calculated using the following formula:
[0252] 14. Neutral Salt Spray Test The neutral salt spray test was conducted in accordance with GB / T 10125—2021, and the test duration was 48 hours.
[0253] After the test, the sample was rinsed with deionized water and left at room temperature for 2 hours before measuring the average reflectance at 450–700 nm.
[0254] Referring to the corrosion defect area and appearance rating principles of GB / T 6461—2002, auxiliary ratings were conducted for visible corrosion spots, discolored areas, and reflective layer defects. Since the silver light pillar film is a polymer-based composite film, color difference and average reflectivity retention were used as the primary evaluation indicators, while the appearance rating served only as a supplementary evaluation result.
[0255] Test Results 1. Rheological, curing and dynamic optical properties Table 4. Rheological, curing, and dynamic optical properties
[0256] Comparative Example 8 omits the interface passivation treatment of the silver reflective layer, while the transparent encapsulation sublayer, ink composition, pigment content, magnetic field orientation conditions, and curing process are all the same as in Example 2. Therefore, the yield stress, viscosity recovery rate, first curing conversion rate, orientation error, and initial dynamic optical properties of Comparative Example 8 are basically the same as those of Example 2.
[0257] Comparative Example 9 omits only the transparent protective layer outside the silver reflective layer. Due to the change in the surface chemical properties of the outermost layer of the silver flake pigment, its dispersion and wetting state and the curing network bonding state are slightly altered. However, its magnetic response layer, pigment size, magnetic field orientation device, and main curing conditions remain unchanged. Therefore, its initial rheological properties and dynamic optical properties are still at the same level as those of Example 2.
[0258] The above results indicate that the performance differences between Comparative Example 8 and Comparative Example 9 in subsequent sulfur-containing gas and salt spray tests are mainly due to the different protective structures of the silver reflective layer, rather than differences in ink rheological properties, magnetic field orientation conditions, or initial dynamic optical properties.
[0259] The non-magnetic silver flake pigment used in Comparative Example 1 has a saturation magnetization of only 0.03 emu / g, which cannot be stably rotated according to the local magnetic field vector. Its average orientation error reaches 18.7°, and it does not form a recognizable continuous flowing light effect.
[0260] Although Comparative Example 2 forms a relatively neat single-angle orientation, it only forms a silver bright band with a basically fixed position because the direction of the magnetic field does not change continuously along the first direction.
[0261] Comparative Example 3 does not have a cylindrical microlens array, and the reflected light generated by the continuous orientation reflection structure is not effectively converged, resulting in a significant reduction in the peak-to-back brightness ratio.
[0262] In Comparative Example 4, the initial curing was insufficient, and the flake-like pigments rotated and partially settled after leaving the magnetic field.
[0263] Comparative Example 5 had an excessively high degree of initial curing. Although the initial dynamic optical performance was still good, the number of unreacted groups retained on the surface of the directional reflective layer decreased, resulting in a decline in interlayer bonding performance.
[0264] Comparative Example 6, which does not contain rheology orientation additives, showed a significant decrease in viscosity recovery and a decline in pigment orientation stability.
[0265] In Comparative Example 7, the angle between adjacent magnetization directions reaches 45°, and the direction of the local magnetic field shows a significant change, resulting in the segmentation and jumping of the light column.
[0266] 2. Mechanical properties and durability Table 5 Adhesion, Hardness, Abrasion Resistance and Solvent Resistance
[0267] Comparative Example 8 still features a transparent encapsulation sublayer containing polymerizable groups, allowing its flake-like pigments to bond with the photocurable resin network. Initial adhesion, hardness, abrasion resistance, and solvent wiping resistance are essentially the same as in Example 2. The omission of the interface passivation treatment primarily affects the long-term optical stability of the silver reflective layer in a sulfur-containing environment, with minimal impact on initial mechanical properties.
[0268] In Comparative Example 9, omitting the transparent protective layer resulted in the silver reflective layer being directly exposed to the ink system, lacking a transparent encapsulation structure on its surface that could participate in photopolymerization. This led to a weakening of the interfacial bonding between the flake pigment and the resin network, a decrease in cross-cut adhesion from grade 0 in Example 2 to grade 1, an increase in abrasion loss from 10.8 mg to 16.8 mg, a decrease in optical retention after abrasion resistance to 86.0%, and a decrease in the number of methyl ethyl ketone (MEK) rub cycles to 110.
[0269] The adhesion of Examples 1 to 6 is all grade 0 to 1, indicating that under the condition of a first photocuring conversion rate of 15% to 45%, the directional reflective layer can not only fix the pigment orientation, but also form a good interlayer bond with the transparent micro-optical modulation layer.
[0270] Comparative Example 4 showed a significant decrease in film hardness, abrasion resistance, and solvent resistance due to insufficient initial curing.
[0271] Although Comparative Example 5 has high hardness, its cross-cut adhesion drops to level 3, and the main failure mode is the local peeling of the transparent micro-optical modulation layer from the surface of the directional reflection layer.
[0272] 3. Anti-discoloration performance of the silver reflective layer Table 6 Results of sulfur-containing gas and salt spray exposure
[0273] In Example 2, after exposure to sulfur-containing gas, the color difference was only 1.6 and the reflectivity retention rate was 96.8%, indicating that the interface passivation sublayer and the transparent encapsulation sublayer can jointly reduce the sulfidation discoloration of the silver reflective layer.
[0274] Although Comparative Example 8 had a transparent encapsulation sublayer, no interface passivation treatment was performed on the silver surface. After exposure to hydrogen sulfide, the color difference increased to 4.9, and the reflectance retention decreased to 88.1%. This result indicates that the transparent encapsulation layer can provide a certain barrier effect, but interface passivation of the silver surface can further suppress the reaction between the sulfur-containing medium and the silver surface.
[0275] Comparative Example 9 did not have a transparent protective layer. After exposure to hydrogen sulfide, the silver reflective layer darkened significantly, and the reflectivity retention rate was only 63.5%, proving that the transparent protective layer has a significant blocking and protective effect on the silver reflective layer.
[0276] Example 6 uses an aluminum reflective layer, which maintains high reflectivity after exposure to sulfur-containing gas and salt spray, indicating that in applications requiring high stability in sulfur-containing environments, the aluminum reflective layer can be used as an alternative to the silver reflective layer.
[0277] 4. Reflectivity and optical properties of the transparent layer Table 7. Properties of Silver Reflective and Transparent Micro-Optical Layers
[0278] The initial reflectivity and peak reflectivity of Comparative Examples 8 and 9 before corrosion exposure were similar to those of Example 2, further illustrating that the differences among the three after exposure to hydrogen sulfide and salt spray were mainly caused by the protective structure of the silver reflective layer.
[0279] The non-magnetic silver pigment used in Comparative Example 1 has a high average reflectivity, but because it cannot form a continuous angular distribution according to the gradient magnetic field, the reflected light from the film surface cannot form a continuously moving light column.
[0280] Comparative Example 3 has the same magnetically responsive pigment and continuous orientation structure as Example 2, but lacks a cylindrical microlens array, and its peak reflectivity and peak-to-back brightness ratio are significantly reduced.
[0281] Figure 1 In the figure, the sample was cut, extracted, and thinned using a focused ion beam, and then observed under an accelerating voltage of 200 kV. In the figure, 1 is the sheet-like transparent substrate, 2 is the magnetic response layer, 3 is the dielectric spacer layer, 4 is the silver reflective layer, 5 is the transparent protective layer, and 6 is the sample preparation protection material or background area. The functional layers are distributed sequentially from the inside out, with clear interlayer interfaces. The scale bar is 50 nm.
[0282] Figure 2 In the figure, after focused ion beam cutting, extraction, and low-voltage thinning, the sample was observed by scanning transmission electron microscopy and energy dispersive spectroscopy at an accelerating voltage of 200 kV. In the figure, 1 is the synthetic mica matrix, 2 is the Fe-enriched magnetic response layer, 3 is the Si and O-enriched dielectric spacer layer, 4 is the Ag-enriched silver reflective layer, 5 is the Si and O-enriched transparent protective layer, and 6 is the sample preparation protective layer or background area; the scale bar is 50 nm.
[0283] Figure 3 The test was conducted at 25±2℃, with an external magnetic field applied. The scanning was performed in the range of 2 to +2 T. The horizontal axis represents the magnetic field strength H, and the vertical axis represents the mass magnetization M. In Example 2, the pigment had a saturation magnetization Ms of 10.6 emu / g, a remanent magnetization Mr of 1.32 emu / g, and a coercivity Hc of 0.082 T, indicating that the pigment has a stable magnetic response capability.
[0284] Figure 4 In the figure, a 532 nm collimated laser is incident along the normal to the film surface, and scattered light is collected from the polished side of the sample. The horizontal axis represents the X-axis position, the vertical axis represents the Z-axis position, and the color represents the normalized relative light intensity. In the figure, 1 is the cylindrical microlens, 2 is the transparent micro-optical modulation layer, 3 is the directional reflection layer, and F is the region of maximum light intensity; the measured focal point is located within the directional reflection layer, with a focal length of approximately 61 μm and a deviation ratio of approximately 4.9%.
[0285] Comprehensive analysis of test results Examples 1 and 3 cover the endpoint regions of ink composition, pigment structure size, film thickness, magnetic field strength, delivery speed and curing energy, respectively, and can still form continuous and identifiable silver light pillars, indicating that the defined numerical range is supported by the corresponding implementation method.
[0286] Example 2 is in the middle range of the main parameters, and obtains an average orientation error of 2.4°, an effective beam displacement of 9.2 mm, a peak-to-backlight ratio of 8.4, and a maximum single-step jump variable of 0.26 mm, with good overall optical performance.
[0287] Example 4 uses an orientation period of 0.8 mm and a soft magnetic plate with periodic magnetic teeth to shape the magnetic flux, demonstrating that a small-period continuous angular orientation structure can still be formed when the center distance of the permanent magnet is greater than the orientation period.
[0288] Example 6 uses an aluminum reflective layer, which can still form obvious dynamic silver light pillars and maintain high reflectivity in sulfur-containing gas and salt spray environments, indicating that the aluminum reflective layer can be used as an alternative implementation method to the silver reflective layer.
[0289] The comparison between Example 2 and Comparative Example 1 shows that silver reflective properties alone are insufficient to form dynamic light pillars; the flake pigment also needs to have effective magnetic responsiveness.
[0290] The comparison between Example 2 and Comparative Example 2 shows that simply arranging the flake pigments neatly is insufficient to form a continuously moving light column; it is also necessary to make the direction of the magnetic field vector continuously change along the first direction.
[0291] A comparison of Example 2 and Comparative Example 3 shows that the continuous orientation of magnetically responsive flake pigments can form a streamer-based structure, and the cylindrical microlens array can further converge angle-selectively reflected light into a high-contrast light column.
[0292] A comparison of Example 2 with Comparative Examples 4 and 5 shows that when the first photocuring conversion rate is below 15%, the pigment orientation retention ability is insufficient; when the first photocuring conversion rate is above 45%, the interlayer co-curing ability and adhesion decrease. A conversion rate range of 15% to 45% achieves a balance between orientation fixation and interlayer bonding.
[0293] The comparison between Example 2 and Comparative Example 6 shows that the yield stress and viscosity recovery ability of the ink directly affect the orientation retention effect of the flake pigment after leaving the magnetic field.
[0294] A comparison of Example 2 and Comparative Example 7 shows that controlling the magnetization direction angle between adjacent permanent magnet units within 5° to 30° helps to form a continuously changing local magnetic field direction; when the angle between adjacent magnetization directions reaches 45°, it is easy to produce beam segmentation and jumps.
[0295] Tables 4, 5, and 7 show that the rheological properties, curing degree, magnetic field orientation effect, and initial dynamic optical properties of Comparative Examples 8 and 9 before corrosion exposure are basically consistent with those of Example 2. Therefore, the differences in the results of sulfur-containing gas and salt spray exposure in Table 6 can be clearly attributed to the single variable of the silver reflective layer protection method.
[0296] The comparison between Example 2 and Comparative Example 8 shows that, under the condition that a transparent encapsulation sublayer is provided in both cases, adding silver surface interface passivation treatment can further reduce the color difference after hydrogen sulfide exposure and improve the reflectivity retention rate.
[0297] The comparison between Example 2 and Comparative Example 9 shows that the transparent protective layer not only provides environmental barrier for the silver reflective layer, but its transparent encapsulation structure containing polymerizable groups can also improve the interfacial bonding between the flake pigment and the photocurable resin network, thereby improving adhesion, abrasion resistance and solvent resistance.
[0298] Therefore, the technical effects of the present invention are jointly produced by the core-shell type magnetically responsive silver flake pigment, the silver reflective layer anti-color change structure, the continuously changing gradient magnetic field, the ink rheological recovery properties, the first partial photocuring, the cylindrical microlens array, and the second complete curing.
Claims
1. A three-dimensional, luminous anti-counterfeiting ink, characterized in that, The ink comprises, by weight percentage: 45%–70% photocurable film-forming component, 10%–25% reactive diluent, 8%–20% core-shell magnetically responsive silver flake pigment, 1%–5% photoinitiator, 0.2%–3% rheology orientation aid, 0.2%–2% dispersing and wetting agent, and 0.2%–5% functional aid. The content of each component is selected within the above range and the total content is 100%. The core-shell magnetically responsive silver flake pigment includes a flake-shaped transparent substrate and, from the inside out, a magnetically responsive layer, a dielectric spacer layer, a silver reflective layer, and a transparent protective layer containing polymerizable groups, which are sequentially coated on the surface of the flake-shaped transparent substrate. The three-dimensional flowing light anti-counterfeiting ink has a yield stress of 2–20 Pa at 25°C, and its viscosity recovery rate after shearing and standing for 60 s is not less than 70%, and it maintains the continuous angular orientation after photocuring.
2. The three-dimensional flowing light anti-counterfeiting ink according to claim 1, characterized in that, The photocurable film-forming component includes aliphatic polyurethane acrylate and hyperbranched polyester acrylate, wherein the mass ratio of aliphatic polyurethane acrylate to hyperbranched polyester acrylate is 2:1 to 8:1; the reactive diluent is selected from two or more of isoborneol acrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate and tripropylene glycol diacrylate.
3. The three-dimensional flowing light anti-counterfeiting ink according to claim 1, characterized in that, The sheet-like transparent substrate is a borosilicate glass sheet or a synthetic mica sheet, with a median particle size D50 of 8–35 μm and a thickness of 0.2–1.0 μm; the thickness of the magnetic response layer is 10–80 nm, the thickness of the dielectric spacer layer is 20–150 nm, the thickness of the silver reflective layer is 20–120 nm, and the thickness of the transparent protective layer is 10–100 nm; the thickness of each coating layer refers to the average thickness measured along the local interface normal direction on one side of the pigment surface.
4. The three-dimensional flowing light anti-counterfeiting ink according to claim 1 or 3, characterized in that, The magnetically responsive layer comprises at least one of iron(II,III) oxide and ferrite; the dielectric spacer layer comprises at least one of silicon dioxide and aluminum oxide; and the silver reflective layer comprises at least one of silver and aluminum. The saturation magnetization of the core-shell magnetically responsive silver flake pigment is 4–18 emu / g, and the average reflectivity of the core-shell magnetically responsive silver flake pigment in the 450–700 nm wavelength band is not less than 60%.
5. A silver columnar film prepared from the three-dimensional luminous anti-counterfeiting ink according to any one of claims 1-4, characterized in that, The system comprises a transparent base film, a base coating, a directional reflective layer, and a transparent micro-optical modulation layer, stacked sequentially. The directional reflective layer contains a core-shell magnetically responsive silver flake pigment, which includes a flake-shaped transparent substrate and a magnetically responsive layer, a dielectric spacer layer, a silver reflective layer, and a transparent protective layer sequentially covering the flake-shaped transparent substrate. A first direction is provided within the surface of the silver light pillar film, and the signed deflection angle of the normal of the core-shell magnetically responsive silver flake pigment relative to the normal of the silver light pillar film surface changes periodically and continuously along the first direction, increasing continuously from a negative value to a positive value and then continuously decreasing in each orientation period. A parallel array of cylindrical microlenses is provided on the side of the transparent micro-optical modulation layer away from the directional reflective layer. The angle between the extension direction of the cylindrical microlenses and the first direction is 70° to 90°. The equivalent focal plane of the cylindrical microlens array is located within the directional reflective layer, or the distance between the equivalent focal plane and the directional reflective layer is no greater than 15% of the equivalent focal length of the cylindrical microlenses.
6. The silver light column film according to claim 5, characterized in that, The normal of the core-shell magnetically responsive silver flake pigment lies within the orientation plane formed by the normal of the silver column film surface and the first direction; the signed deflection angle refers to the deflection angle of the normal of the core-shell magnetically responsive silver flake pigment relative to the normal of the silver column film surface, wherein the deflection angle when the normal deflects from the film surface normal to the positive side of the first direction is a positive value, and the deflection angle when the normal deflects from the film surface normal to the opposite side of the first direction is a negative value; the signed deflection angle is -35° to 35°, the orientation period is 0.8 to 10 mm, and the gradient of the signed deflection angle along the first direction is 2° / mm to 20° / mm; the pitch of the cylindrical microlens array is 30 to 150 μm, the bow height is 5 to 40 μm, and the radius of curvature is 15 to 100 μm.
7. The silver light column film according to claim 5 or 6, characterized in that, The transparent base film is selected from one of polyethylene terephthalate film, biaxially oriented polypropylene film, polycarbonate film, and polyamide film, and the thickness of the transparent base film is 12-100 μm; the thickness of the base coating is 0.3-3 μm; the thickness of the directional reflective layer is 2-20 μm; the thickness of the transparent micro-optical modulation layer is 25-200 μm; a transparent wear-resistant layer is also provided outside the transparent micro-optical modulation layer to maintain the contour of the cylindrical microlens array, and the thickness of the transparent wear-resistant layer is 0.5-5 μm.
8. The method for preparing the silver beam film according to any one of claims 5-7, characterized in that, Includes the following steps: S1. A core-shell type magnetically responsive silver flake pigment having a magnetically responsive layer, a dielectric spacer layer, a silver reflective layer and a transparent protective layer is mixed with a reactive diluent and a dispersing and wetting agent to form a pre-dispersion. Then, a photocurable film-forming component, a photoinitiator and a rheology orientation aid are added to the pre-dispersion, and a three-dimensional flowing light anti-counterfeiting ink is obtained after degassing treatment. S2. Apply the three-dimensional flowing light anti-counterfeiting ink to the surface of the transparent base film after primer treatment to form an uncured ink layer; S3. The uncured ink layer is passed through a gradient magnetic field orientation device, which includes multiple strip-shaped permanent magnet units arranged sequentially along a first direction within the transparent base film surface. The magnetization direction of each strip-shaped permanent magnet unit is located within an orientation plane formed by the normal of the transparent base film surface and the first direction. During each magnetic field direction change cycle, the magnetic field direction angle corresponding to each magnetization unit or magnetically conductive unit gradually increases from a negative value to a positive value, and then gradually decreases from a positive value to a negative value. The difference in magnetic field direction angle between adjacent measurement positions is no greater than 30°, the difference in magnetic field direction angle at the boundary of adjacent cycles is no greater than 30°, and the center distance between two adjacent strip-shaped permanent magnet units is 5-30 mm, so as to form a gradient magnetic field with a continuously changing magnetic field direction along the first direction at the location of the uncured ink layer. The gradient magnetic field is used to form a periodic continuous angular distribution of the normal of the core-shell magnetically responsive silver flake pigment, and the uncured ink layer is photocured for the first time while maintaining the gradient magnetic field to fix the periodic continuous angular distribution. S4. A transparent photocurable resin is coated on the surface of the ink layer that has undergone the first photocuring. A parallel array of cylindrical microlenses is formed on the surface of the transparent photocurable resin using a microstructure mold, such that the angle between the extension direction of the cylindrical microlens array and the first direction is 70° to 90°. Then, a second photocuring is performed to obtain the silver light column film.
9. The preparation method according to claim 8, characterized in that, The core-shell type magnetically responsive silver flake pigment in step S1 is prepared by the following steps: forming a magnetically responsive layer containing iron(III) oxide on the surface of a flake-shaped transparent substrate through a co-precipitation reaction; forming a silica dielectric spacer layer on the surface of the magnetically responsive layer using a sol-gel method; forming a silver or aluminum silver reflective layer on the surface of the dielectric spacer layer using magnetron sputtering or chemical plating; and coating the silver reflective layer with a silane coupling agent containing methacryloxy group to form a transparent protective layer containing polymerizable groups.
10. The preparation method according to claim 8, characterized in that, The thickness of the uncured ink layer formed in step S2 is 3–20 μm; in step S3, the magnetic induction intensity at the location of the uncured ink layer is 60–250 mT, the magnetic field gradient is 5–35 mT / mm, the distance between the working surface of the gradient magnetic field orientation device and the uncured ink layer is 1–8 mm, and the transport speed of the transparent base film is 5–60 m / min; the first photocuring uses ultraviolet light with a wavelength of 365–405 nm and an irradiation energy of 20–150 mJ / cm², and by controlling the irradiation energy and the transport speed of the transparent base film, the conversion rate of polymerizable unsaturated double bonds in the uncured ink layer reaches 15%–45%; the irradiation energy of the second photocuring is 300–1200 mJ / cm².